2016
DOI: 10.17221/434/2015-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive compounds and antioxidant activity of mung bean (Vigna radiata L.), soybean (Glycine max L.) and black bean (Phaseolus vulgaris L.) during the germination process

Abstract: Xue Z., Wang C., Zhai L., Yu W., Chang H., Kou X., Zhou F. (2016): Bioactive compounds and antioxidant activity of mung bean (Vigna radiata L.), soybean (Glycine max L.) and black bean (Phaseolus vulgaris L.) during the germination process. Czech J. Food Sci., 34: 68-78.Bioactive compounds and antioxidant activity of germinated mung bean, soybean and black bean sprouts were investigated to find out the effect of germination and the optimum germination time. We found that vitamin C gradually increased from zero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
0
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 45 publications
5
42
0
9
Order By: Relevance
“…Compared to TPC, there are fewer reports about the effect of germination on the TFC of common beans. Xue et al (2016) showed that the TFC of black beans increased with the increase of germination time and reached the highest value on the 5th day.…”
Section: Germinationmentioning
confidence: 96%
See 2 more Smart Citations
“…Compared to TPC, there are fewer reports about the effect of germination on the TFC of common beans. Xue et al (2016) showed that the TFC of black beans increased with the increase of germination time and reached the highest value on the 5th day.…”
Section: Germinationmentioning
confidence: 96%
“…Xue et al. () showed that the TFC of black beans increased with the increase of germination time and reached the highest value on the 5th day.…”
Section: Factors Influencing Phenolic Content and Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in phenolic and flavonoid content and AoxA in chickpea seeds shows a potentially important role of phenolics during seed germination, as well as the potential enhancement of the nutraceutical value of seeds by the germination process (Cevallos-Casals & Cisneros-Zevallos, 2010). Xue et al (2016) carried out a study on bioactive compounds and antioxidant activity of mung and black bean, and soybean during the germination process. They reported, after an analysis of relative contribution, that total phenolics and total flavonoids made the highest (44.87-90.31%) contribution to overall antioxidant activity.…”
Section: Phenolic Content Flavonoid Content and Antioxidant Activitymentioning
confidence: 99%
“…For example, we presented a positive correlation between TPC and anti‐oxidative capacity (Fig. ), in agreement with well‐established findings that phenolic compounds in grain legumes contribute to their antioxidant capacity . The variation observed also suggests that TPC is a valid target for selection within breeding programs.…”
Section: Discussionmentioning
confidence: 99%